2011
DOI: 10.3329/bsmmuj.v4i2.8636
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Morbidity in Psoriasis and Vitiligo in Two Tertiary Hospitals in Bangladesh

Abstract: Abstract:Background: Many of the established skin diseases give rise to psychiatric disorders notably psoriasis and vitiligo. In Bangladesh, no study has yet been reported on psychiatric morbidity among psoriasis and vitiligo patients. Objectives: The objective of the study was to see the psychiatric morbidities in two chronic skin diseases, psoriasis and vitiligo, in Bangladesh. Methods: This was a cross sectional, analytical and comparative study. It was conducted to see whether psychiatric morbidity was hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…However, few studies have found lower prevalence of psychological morbidity of 31%, 24%, 42%, and 10% using different assessment tools such as Structured Clinical Interview for Diagnostic and Statistical Manual-IV Axis I Disorders (SCID-1) and psychiatric assessment schedule. [ 15 16 17 18 ] Higher prevalence of psychiatric morbidity (79.2%) was found in a study done by Ramakrishna and Rajni using the Rosenberg self-esteem scale and Hamilton depression rating scale. [ 19 ] The use of different diagnostic tools may be the cause of the differences in the prevalence of psychiatric morbidity in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have found lower prevalence of psychological morbidity of 31%, 24%, 42%, and 10% using different assessment tools such as Structured Clinical Interview for Diagnostic and Statistical Manual-IV Axis I Disorders (SCID-1) and psychiatric assessment schedule. [ 15 16 17 18 ] Higher prevalence of psychiatric morbidity (79.2%) was found in a study done by Ramakrishna and Rajni using the Rosenberg self-esteem scale and Hamilton depression rating scale. [ 19 ] The use of different diagnostic tools may be the cause of the differences in the prevalence of psychiatric morbidity in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…11 Rashid et al reported majority (36%) between 35-44 years. 10 In this study 42 (84.0%) male and 8 (16.0%) female in the psoriasis group; whereas 41 (82.0%) male and 9 (18.0%) female in the control group that was insignificant (p=0.790).…”
Section: Resultsmentioning
confidence: 45%
“…This result correlated with Rashid et al where in psoriasis patients male were 36 (72.0%) and female 28 %. 10 Paul reported on his study male 10 (52.6%) and female 9 (47.4%) in psoriasis patients. 11 Regarding the marital status, current study showed that 35 (70.0%) respondents were married and 12 (24.0%) respondents were unmarried in psoriasis group.…”
Section: Resultsmentioning
confidence: 90%
“…BDI scores were the highest in psoriasis group but this difference was not significant (P = 0.2). Rashid et al (2011) Bangladesh Vitiligo and Psoriasis 50 patients with psoriasis 35.32±10.05 years and same number of patients with vitiligo 33.50±9.99 years and were compared Diagnostic and Statistical Manual for Mental and Behavioural Disorders-Fourth Edition) DSM-IV The proportion of major depressive disorders (MDD) was higher among psoriasis patients 15(30.0%) compared to vitiligo patients 04(8.0%). However, no statistical difference was found between two groups of patients in terms of anxiety disorders (8% in psoriasis and 12% in vitiligo patients).…”
Section: Resultsmentioning
confidence: 99%